Meta-Analysis of 3D Printing Applications in Traumatic Fractures - Yang, Sha; Lin, Huapeng; Luo, Cong (Frontiers in Surgery, 2021)
Background: Traumatic fracture is a common orthopaedic disease, and application of 3D printing technology in fracture treatment, which entails utilisation of pre-operative printed anatomic fracture model, is increasingly gaining popularity. However, effectiveness of 3D printing-assisted surgery lacks evidence-based findings to support its application. Materials and Methods: Embase, PubMed and Cochrane Library databases were systematically searched until October, 2020 to identify relevant studies. All randomised controlled trials (RCTs) comparing efficacy of 3D printing-assisted surgery vs. conventional surgery for traumatic fractures were reviewed. RevMan V.5.3 software was used to conduct meta-analysis. Results: A total of 12 RCTs involving 641 patients were included. Pooled findings showed that 3D printing-assisted surgery had shorter operation duration [standardised mean difference (SMD) = −1.52, 95% confidence interval (CI) – 1.70 ~ −1.34, P < 0.00001], less intraoperative blood loss (SMD = 1.34, 95% CI 1.74 ~ 0.94, P < 0.00001), fewer intraoperative fluoroscopies (SMD = 1.25, 95% CI 1.64 ~ 0.87, P < 0.00001), shorter fracture union time (SMD = −0.15, 95% CI −0.25 ~ −0.05, P = 0.003), and higher rate of excellent outcomes (OR = 2.40, 95% CI 1.07 ~ 5.37, P = 0.03) compared with conventional surgery. No significant differences in complication rates were observed between the two types of surgery (OR = 0.69, 95% CI 0.69 ~ 1.42, P = 0.32). Conclusions: Indicators including operation duration, intraoperative blood loss, number of intraoperative fluoroscopies, fracture union time, and rates of excellent outcomes showed that 3D printing-assisted surgery is a superior alternative in treatment of traumatic fractures compared with conventional surgery. Moreover, the current study did not report significant differences in incidence of complications between the two approaches. Systematic Review Registration: CRD42021239507.